Performance Evaluation of DDS-Based Middleware over Wireless Channel for Reconfigurable Manufacturing Systems - Basem Almadani; Muhammad Naseer Bajwa; Shuang-Hua Yang; Abdul-Wahid A. Saif (International Journal of Distributed Sensor Networks)
Reconfigurable manufacturing systems (RMS) are rapidly becoming choice of production and manufacturing industry due to their quick adaptability to the ever-changing market demands while maintaining the quality and cost of the products. Such systems are usually decentralized in their monitoring and control and consist of heterogeneous components. Therefore, need arises for an interface that can mask the heterogeneity and provide smooth communication among these dissimilar components. Data Distribution Service (DDS) is a data-centric middleware standard based on Real-Time Publish/Subscribe (RTPS) protocol that fulfills the job of such interface in distributed systems. In this work, we present the idea of using DDS-based middleware over commonly used wireless channels like Bluetooth and Industrial WiFi to facilitate data communication in distributed control systems. A simulation model is developed to quantify various performance measures like latency, jitter, and throughput and to examine the suitability of aforementioned wireless channels in distributed monitoring and control environments. The model explores various communication scenarios based upon a practical case study. Obtained results serve as an empirical proof of concept that DDS can ensure reliable and timely data communication in firm real-time distributed control systems using common wireless channels and offer extensive control over various aspects of data transmission through its rich set of QoS policies.